Profissionalização docente e formação continuada: uma análise desses conceitos no mapa de competências do Programa Ensino Integral do estado de São Paulo - Souza, Adriele Longo de. (2024)
This study offers a perspective on professional development frameworks within public policy, aiming to unveil intrinsic and underlying aspects in official documents that permeate teaching practices. Thus, this approach seeks to foster critical analysis with a view to strengthening the movement toward teacher professionalization. Accordingly, the research examines the premise of continuing education within the Competency Map of PEI (Integral Education Program) through a bibliographic review of field research and studies, assessing the extent to which this document supports the foundations of teacher professionalization. The investigation is grounded in the epistemology of practice as its theoretical framework, drawing on authors such as Perrenoud (1999; 2000), Machado (2002), Dutra (2010), and Dias (2010) to discuss the concept of competencies; Imbernón (2011) and Nóvoa (1992, 2017) to address the concept of continuing education; and Imbérnon (2011), Marcelo (2009), Thurler (2002), Tardif (2012, 2013, 2014), Gauthier et al (1998), Contreras (2002), and Gatti (2010) in order to focus on professional development and teacher professionalization. Following a qualitative approach based on Lüdke and André (1986) and Gil (2008), along with an exploratory-descriptive study design (SELLTIZ et al, 1965), the research was conducted through documentary analysis (Gil, 2017) of materials related to the PEI, specifically focusing on the Competency Map and its premise regarding continuing education, alongside a literature review of research (2012-2023) and authors in the field of teacher professionalization. The analyzed data were organized into four analytical axes: Axis 1 – Competencies; Axis 2 – Continuing education and knowledge mastery; Axis 3 – Continuing education and self-development; and Axis 4 – Teacher professionalization. The first three axes were developed based on the principles outlined in the Competency Map, while the last one stemmed from a perspective advocating for an epistemology of professional practice. The analyses revealed that although the Competency Map and PEI recognize the importance of continuing education, the predominant approach has been technical, focused on practical and observable institutional knowledge, thus limiting the full realization of teacher professionalization. This technicist perspective, associated with the phenomenon of proletarianization and rationalization of teaching, disregards reflective, critical, and autonomous aspects essential for professionalization. Therefore this research is expected to contribute to critical reflection on the teacher professionalization movement of professionals working within PEI, recognizing the importance of autonomy and valuing the knowledge produced and mobilized by teachers in their work contexts. Keywords: Integral Education Program (PEI); Competency Map; Continuing Education; Teacher Professionalization.